Gender mainstreaming in development organisations: policy, practice and institutional change. - Piálek, N (University of Oxford;Department for International Development (DFID), QEH, 2008)
‘Gender and Development’ (GAD) is currently seen as the dominant theoretical model within international development for promoting social justice and equality for women. As a consequence, many development organisations are undertaking gender mainstreaming. The most interesting fact about the vast number of analyses about gender mainstreaming is the consistency with which they tell of GAD influenced policies failing to implement GAD approaches in practice. This should raise suspicion rather than simple condemnation. It is time to ask: ‘How are, often very progressive, gender policies and strategies consistently silenced across the range of organisational contexts?’ This thesis focuses upon the contemporary process of gender mainstreaming in development organisations – a term that specifically refers to a ‘process of organisational change’ that aims to explicitly develop the ‘use of GAD approaches within all projects and programmes’ of development institutions in order to achieve ‘a vision of development that creates gender equitable social change’ in society. Moreover, it takes an approach that specifically details the ‘organisational process’ element of change inferred in the term. As such, this thesis uses the literature of organisational culture as a lens to make previously unnoticed and submerged sites of conflict and acts of resistance visible, allowing an understanding to be gained of how gender mainstreaming has so consistently faced a policy-practice impasse. It develops this analysis using an in-depth case study of Oxfam GB and demonstrates that the process of gender mainstreaming in the organisation has resulted in the removal of ‘responsibility for’ implementing GAD approaches among staff in the organisation. It goes on to highlight that the unwillingness of development organisations and practitioners to recognise gender mainstreaming as an explicitly feminist and political process of change directly couched at the level of the organisation and not just at the level of the actual development project (or society more widely) has resulted in the ‘process of organisational change’ becoming rationalised and technical rather than personal and politically charged. In reaching this understanding of gender mainstreaming, the thesis develops an awareness of organisational change processes and highlights that ‘norms’ and ‘values’ in organisations are often confused. This confusion has led to an ineffective process of change in institutions as well as a poor conceptualisation and practice of gender mainstreaming in international development.